Coevolution influences the evolution of filial cannibalism, offspring abandonment and parental care. Issue 1909 (21st August 2019) - Klug, Hope; Bonsall, Michael B.
Abstract : Understanding evolutionary patterns of parental investment and care has been a long-standing focus in studies of evolutionary and behavioural ecology. Indeed, patterns of investment and care are highly diverse, and fully understanding such diversity has been challenging. Recently, several studies have highlighted the need to consider coevolutionary dynamics in studies of parental care, as parental care is likely to co-occur and co-originate with a range of other traits. Two traits that commonly co-occur with parental care are offspring abandonment (the termination of parental investment prior to full independence in offspring) and filial cannibalism (the consumption of one's offspring). Here, we use a mathematical framework to explore how co-occurrence and coevolution among care, abandonment and cannibalism can influence the life-history conditions under which care is expected to evolve. Our results suggest that in some cases, the evolution of parental care can be inhibited by offspring abandonment and filial cannibalism. In other cases, abandonment and filial cannibalism that benefits parents can promote the evolution of parental care. It is particularly interesting that behaviours that seem so contrary to care—that is, eating or abandoning one's young—can in some cases broaden the conditions under which care can evolve. In general, our findings highlight that considering co-occurrence and coevolutionary dynamics between two or more traits is essential to understanding the evolution of trait diversity.